Sharia Controls For Islamic Companies In Islamic Jurisprudence (Journal of the College of Basic Education, 2026)
Since the beginning of creation and the existence of man on the face of the earth, he has needed to cooperate with his fellow man in order to continue living, and this cooperation has taken various forms and shapes. Because of this need, a type of interaction has existed among people since ancient times that they called (the company). The concept of the company has developed over the ages, and its forms and shapes have expanded and multiplied. Islam came and found that companies existed among the Arabs, as they had an important commercial activity, so it legislated dealing in companies and set its rules and regulations. People increased in number and their needs increased and expanded, so dealing in companies expanded with them and took on various forms, some of which were permissible and some of which were not.In this research, we shed light on the most important types of Islamic companies, their concepts, controls, and conditions, considering them an important means of developing the Islamic economy in Islamic societies and beyond.